Insights to maternal regulation of the paternal genome in mammalian livestock embryos: A mini-review - Daigneault, Bradford W. (Frontiers in Genetics, 2022)
This mini-review focuses on current knowledge regarding maternal regulation of the paternal genome in early embryos of mammalian livestock species. Emphasis has been placed on regulatory events described for maternally imprinted genes and further highlights transcriptional regulation of the post-fertilization paternal genome by maternal factors. Specifically, the included content aims to summarize genomic and epigenomic contributions of paternally expressed genes, their regulation by the maternal embryo environment, and chromatin structure that are indispensable for early embryo development. The accumulation of current knowledge will summarize conserved allelic function among species to include molecular and genomic studies across large domestic animals and humans with reference to founding experimental animal models.